2023
DOI: 10.3390/cosmetics10040094
|View full text |Cite
|
Sign up to set email alerts
|

Hydrobiome of Thermal Waters: Potential Use in Dermocosmetics

Abstract: Over the course of the last 20 years, numerous studies have identified the benefits of thermal waters on different skin conditions. Consequently, several investigations have been carried out on their effects on the skin, which are linked to their chemical composition, and, recently, scientists have turned their attention to the role of the thermal spring’s microbiota, named “hydrobiome”, regarding these therapeutic effects. At the same time, the development of cosmetics based on pre, pro, and postbiotics has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…In this scenario, we presented the analysis of a spring water, LS-TSW, which emerges in the region of Cantabria, in the north of Spain. Under our analysis, LS-TSW is classified as chloride, sodium, sulphate, bicarbonate, calcium, and magnesium mineral water [15,21]. Comparing with other thermal spring waters used in dermocosmetics and skin care, due to its high chloride content, it could be of interest in the treatment of different skin disorders, such as psoriasis and sensitive skin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this scenario, we presented the analysis of a spring water, LS-TSW, which emerges in the region of Cantabria, in the north of Spain. Under our analysis, LS-TSW is classified as chloride, sodium, sulphate, bicarbonate, calcium, and magnesium mineral water [15,21]. Comparing with other thermal spring waters used in dermocosmetics and skin care, due to its high chloride content, it could be of interest in the treatment of different skin disorders, such as psoriasis and sensitive skin.…”
Section: Discussionmentioning
confidence: 99%
“…With some of these features, it has been declared as medicinal mineral water by the IGME (Instituto Geológico y Minero de España) and the Department of Industry (Autonomous Government of Cantabria). According to the mineral content, La Solia TSW is classified as chloride, sodium, sulphate, bicarbonate, calcium, and magnesium mineral water [15,21]. Many beneficial properties have been assigned to different spring waters.…”
Section: La Solia Thermal Spring Water Chemical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, in vivo investigations were conducted using a dermocosmetic formulation (M89PF) comprising 80% Vichy mineral water, 5% V. filiformis lysate (cultivated in Vichy mineral water), 4% niacinamide (vitamin B3), 0.4% hyaluronic acid, and 0.2% vitamin E. The aim was to assess the clinical effectiveness in preventing and repairing stressed skin. Findings revealed that the M89PF dermocosmetic formulation significantly expedited skin renewal in comparison to untreated skin [12]. These substances have been found to have various effects on the skin, such as moisturizing and sterilizing effects.…”
Section: Introductionmentioning
confidence: 99%